Faktor Lingkungan yang Berhubungan dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita - Fitri, Rahmi Pramulia; Fitriani, Iyang Maisi; Aryana, Indry (Universitas Riau, 2020)
All deaths caused by ARI cover 20% -30% per year (Rasmaliah, 2004). Risk factors contributing to ARI include poor nutrition, low exclusive breastfeeding, indoor air pollution, density, low measles immunization coverage, and LBW (WHO, 2007). Residential density in the home needs to be taken into account because it has a role in the spread of microorganisms within the home or residence environment. 58.9%. The purpose of this study was to determine the environmental factors associated with the incidence of Acute Respiratory Infection (ARI) in Toddlers in the Work Area of the Republic of Indonesia Simpang Tiga City Health Center in Pekanbaru with quantitative approaches and social methods. The total population of 1658 children under five in 2015 with a sample of 94 people. The results obtained are related to cigarette smoke exposure with ARI in toddlers in the Simpang Tiga RI Puskesmas Work Area, meaning that those who get cigarette smoke exposure from one of their family members who smoke are 3 times more likely to get ARI than those who do not get cigarette smoke exposure from either one family member smokes. There is no relationship between house ventilation and ARI events in toddlers in the Puskesmas RI Simpang Tiga City in Pekanbaru in 2016. There is a relationship between occupancy density and ARI events in toddlers in the Puskesmas RI Simpang Tiga working area, meaning that densities his home occupancy does not meet the risk of being 8 times more affected by ARI compared to the density of his residential occupancy which meets the requirements.